2012
DOI: 10.1159/000341444
|View full text |Cite
|
Sign up to set email alerts
|

Matrine Inhibits Breast Cancer Growth ViamiR-21/PTEN/AktPathway in MCF-7 Cells

Abstract: Background: Matrine is one of the major alkaloids extracted from Sophora flavescens and has been used clinically for breast cancer with notable therapeutic efficacy in China. However, the mechanisms are still largely unknown. Methods: Cell viability was analyzed by MTT assay. After MCF-7 cells were treated with matrine for 48h, apoptosis was detected by flow cytometry, TUNEL assay and transmission electron microscopy, and the cell cycle distribution was also analyzed by flow cytometry. Further, the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 30 publications
8
89
1
Order By: Relevance
“…Numerous studies have demonstrated that matrine possesses numerous biological activities, including antitumor, antivirus, antioxidant and anti-inflammatory actions (3,(6)(7)(8)12). However, the effects of matrine on heart failure have not previously been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that matrine possesses numerous biological activities, including antitumor, antivirus, antioxidant and anti-inflammatory actions (3,(6)(7)(8)12). However, the effects of matrine on heart failure have not previously been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Matrine is able to inhibit cell proliferation and induce the apoptosis of acute myeloid leukemia cells via the mitochondrial pathway and Akt inactivation (7). Furthermore, the growth of MCF-7 breast cancer cells was also inhibited by matrine via the miR-21/PTEN/Akt pathway (8). Additionally, matrine exhibited antinociceptive effects on neuropathic pain induced by chronic constriction injury in mice (9).…”
Section: Introductionmentioning
confidence: 99%
“…Matrine might repress the expression of miR-21, which can target and down-regulate the tumor suppressor PTEN. The upregulation of PTEN dephosphorylates Akt, resulting in an accumulation of Bad, p21/WAF1/CIP1 and p27/KIP1, which trigger intrinsic apoptotic cascades [13] . Matrine can also inhibit cell proliferation and induce apoptosis in a dose-and time-dependent manner in gastric carcinoma cells (SGC-7901).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that matrine possesses a wide range of pharmacological activities, and its antitumor activity has attracted considerable attention in recent years. Cumulative data have demonstrated that matrine exerts anticancer effect on many series of human cancer cells including lung cancer (16), hepatoma (16), breast cancer (17), pancreatic cancer (18), prostate cancer (19,20) and colon cancer (21). Upregulation of protein E2F-1 and activation of caspases contribute to matrine-induced leukemia cell proliferation inhibition and apoptosis (15).…”
Section: Introductionmentioning
confidence: 99%